Indonesia Economic Quarterly, July 2014 : Hard Choices - World Bank (Washington, DC, 2014)
The Indonesia Economic Quarterly (IEQ) has two main objectives. First, it reports on the key developments over the past three months in Indonesia's economy, and places these in a longer term and global context. Based on these developments, and on policy changes over the period, the IEQ regularly updates the outlook for Indonesia's economy and social welfare. Second, the IEQ provides a more in-depth examination of selected economic and policy issues, and analysis of Indonesia s medium-term development challenges. It is intended for a wide audience, including policymakers, business leaders, financial market participants, and the community of analysts and professionals engaged in Indonesia's evolving economy. As Indonesians await the results of a presidential election on July 9, 2014 and plan for the upcoming inauguration of a new president in October, they face hard policy choices. The past decade of solid growth has contributed to considerable development progress. Indonesia now has the world's tenth largest economy in purchasing power parity-adjusted terms; however, there remains a clear risk that the recent moderation in economic growth could intensify. Against a backdrop of weakening revenue growth and rising energy subsidy spending, this would further constrain development expenditures in critical areas such as infrastructure, social protection and health. The new government will face an evolving global environment, which is expected to pick up speed later this year. The price of Indonesia's top six exports, accounting for 50 percent of total export revenues, continues to soften, falling by 8.6 percent in 2014 through June, led by coal (down 15.2 percent). The recent volatility of oil prices, due in part to the turmoil in Iraq, highlights the ongoing vulnerability of Indonesia's fiscal position to higher international oil prices. Real GDP growth in Indonesia moderated to 5.2 percent year-on-year and 4.3 percent quarter-on-quarter at a seasonally-adjusted annualized rate in the first quarter of 2014. Safeguarding hard-fought poverty reduction and social protection progress in Indonesia also calls for enhancing the management of disaster risks. This edition of the IEQ examines one such disaster risk: forest and land fires.